Hospital discharge: testing the “Blaylock Risk Assessment Screening Score” in a surgical department - Colognesi, Sara; Fagnani, Cristina; Panceri, Federica; Ruggero, Manuela; Di Florio, Filomena; Passoni, Chiara; Fantini, Valentina; Boracchi, Patrizia; Orenti, Annalisa; Fumagalli, Maria Adele; Vergani, Marco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work Standardizing patients’ assessment to identify individuals at greater risk in encountering difﬁculties at discharge may help to assist healthcare professionals in clinical decision making and address the gaps in quality that negatively affect continuity of care. We analyzed the predictive validity and the test-retest reliability of the BRASS index in surgical inpatients. Moreover, we evaluated the association between other variables and length of stay or location at discharge. Methods A prospective observational study was conducted. Four hundred twenty-eight patients (≥18 years old) hospitalized in the surgical department of Vimercate hospital were recruited. Data were collected using BRASS index within 48 hours from admission and before discharge. Results We found a high specificity for BRASS in identifying patients discharged to their home with assistance or to residential care. The hospital stay for medium and high-risk patients was signiﬁcantly longer than those in the low-risk group. There was no statistically significant difference of the BRASS scores during hospitalization. Type of admission, pressure ulcers, ASA score, multidrug-resistant bacterial infections, medical complications and Intensive Unit Care stay showed a significant correlation with longer hospitalization and increased probability to be discharged to their home with assistance or to residential care. Conclusions The BRASS Index may support healthcare professionals to identify surgical inpatients requiring a discharge planning and needs to be completed just once at admission. The inclusion of other patient-specific factors in the assessment process could be valuable for targeting the at-risk population.